Running off the rails. - Eastham, T.R.
High-speed rail works well in Europe and Japan, so why can't the United States get it right? The outlines the problems faced by railways in the US, highlighting the case of Amtrak's Acela Express fleet which were taken out of service after only twenty months due to a major fault; 200 comparatlively minor defects were also identified. One of the main reasons for the problems with railways in the US Northeast corridor is that a new dedicated track alignment was not possible and speed restrictions are in force in densely populated regions. In retrospect, some problems were to be expected, considering that an unproven advanced-technology train was being introduced on an existing, if upgraded, infrastructure. Despite these teething troubles, Acela Express is a success. The Northeast corridor is the proving ground for high-speed rail in North America, from both technical and marketing perspectives. For the sake of sustainable mobility in an environmentally acceptable manner, high-speed rail must be the way forward in North America,.
Keywords: Acela Express; Amtrak; US Northeast corridor; Densely populated regions; High-speed railways; Speed restrictions; Track alignment